Transport of Anti-Glycoprotein IIb/IIIa-Antibodies into the Alpha-Granules of Unstimulated Human Blood Platelets - Morgenstern, Eberhard; Ruf, Andreas; Patscheke, Heinrich (Thrombosis and Haemostasis, 1992)
The redistribution of the antibody-glycoprotein (GP) IIb/IIIa complex was investigated with the immuno-gold labeling technique in order to trace its transport in resting platelets. Washed platelets were incubated in the presence of aspirin and a prostacyclin analogue (iloprost) with three different monoclonal antibodies (Gi3, J15 and P2) against GPIIb/IIIa. The examination of ultrathin serial sections showed that the surface labeling was internalized into the surface connected membrane system (SCS). Labels were found within the alpha-granules after 40 min and the number of labels increased during longer incubation periods (max. 120 min). The transport possibly involved coated membranes. The alpha-granules were neither found to be altered during this process nor were any morphological signs of platelet activation detectable. The anti-GPIIb/IIIa complex remained membrane-associated during the transfer. These observations indicate that the membrane-GPIIb/IIIa complex was stable and transported from the surface into the alpha-granules of resting platelets. Since this transport was not influenced by iloprost or by aspirin it may be interpreted as constitutive endocytosis.